Humor Techniques in a Collection of Anecdotal Texts from dari Canda Nabi dan Sufi Sampai Kelucuan Kita by Mustofa Bisri - Islami, Toat Abdaul; Andayani; Rohmadi, Muhammad (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The realization of humor texts can be used to examine anecdotal texts in order to make new findings from the perspective of linguistics and humor. Sufi humor is the basis of the anecdote text chosen because it contains references to religious messages, history, and the condition of past society. This study aims to identify humor techniques and their functions in the anecdotal texts From the Jokes of the Prophet and Sufis to Our Jokes by Mustofa Bisri. The research approach applied is content analysis with Berger's Logic Humor Technique. The data sources are 5 anecdotal texts that contain logical humor from 70 texts in From the Jokes of the Prophet and Sufi to Our Jokes by Mustofa Bisri. Purposing sampling was used for sampling technique. The data collection used document analysis, while the data validity test used theoretical triangulation. The data analysis used a flowing model. The results showed four logical humor techniques in the anecdotal texts From the Jokes of Prophets and Sufis to Our Jokes by Mustofa Bisri, namely ignorance, repetition, absurdity, and mistake. In addition, the humor logic used focuses on the mindset and ridiculous actions performed by the characters in the anecdote text. Logic in humor is different from the logic generated from ordinary human thinking so that jokes can be produced. The results of this study can be used as Sufi literacy media in the world of education. Logical humor techniques are reinforced by psychological findings that point to the absurd thinking and actions performed by the characters. he study about anecdotal texts from Dari Canda Nabi & Sufi sampai Kelucuan Kita can be the learning recourse reference for the students and the society in general. Hopefully, the application of the humor technique in the anecdotal text study can be the study reference for similar humir study so that the anecdotal text study is not limited on its learning method, but the students can comprehend the essence, structure, and humor technique stated in the anecdotal texts.